BIOMORPHOLOGICAL AND BIOCHEMICAL PECULIARITIES OF THE GROWTH AND DEVELOPMENT OF THE SPECIES Elsholtzia ciliata (Thunb.) Hyl. UNDER THE PEDOCLIMATIC CONDITIONS OF THE REPUBLIC OF MOLDOVA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2021)
The paper presents a detailed study on the biology and chemical composition of the essential oil produced by the species Elsholtzia ciliata (Thunb.) Hyl., which has been researched in the Botanical Garden as a medicinal, aromatic and spicy plant. It is a new and promising species in the field of aromatherapy and phytotherapy. The essential oil has antibacterial, antiviral, astringent, carminative, diuretic and stomachic effects. E. ciliata is used as flavouring in food, as an ornamental plant or as a natural air freshener. Keywords: plant, essential oil, components, chromatography, aromatherapy, properties, compounds